2017
DOI: 10.1186/s12877-017-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

Dying comfortably in very old age with or without dementia in different care settings – a representative “older old” population study

Abstract: BackgroundComfort is frequently ranked important for a good death. Although rising numbers of people are dying in very old age, many with dementia, little is known about symptom control for “older old” people or whether care in different settings enables them to die comfortably. This study aims to examine, in a population-representative sample, associations between factors potentially related to reported comfort during very old people’s final illness: physical and cognitive disability, place of care and transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 113 publications
0
23
0
2
Order By: Relevance
“…Older people's dying and death usually takes the form of a process over a period of time (Covinsky, Eng, Lui, Sands, & Yaffe, 2003;Ross, Fisher, & Maclean, 2000). A study of older people's dying and death found that most older people are disabled in their last year of life and common symptoms they might have are distress, pain, depression and confusion (Fleming et al, 2017). However, older people's deaths have been identified as being difficult to predict and a study by Barclay et al (2014) found that, in a nursing home, being able to recognize when an older person was dying varied from case to case.…”
Section: Older People's Dying and Deathmentioning
confidence: 99%
“…Older people's dying and death usually takes the form of a process over a period of time (Covinsky, Eng, Lui, Sands, & Yaffe, 2003;Ross, Fisher, & Maclean, 2000). A study of older people's dying and death found that most older people are disabled in their last year of life and common symptoms they might have are distress, pain, depression and confusion (Fleming et al, 2017). However, older people's deaths have been identified as being difficult to predict and a study by Barclay et al (2014) found that, in a nursing home, being able to recognize when an older person was dying varied from case to case.…”
Section: Older People's Dying and Deathmentioning
confidence: 99%
“…Regardless of the facts that 38% of all deaths in Sweden occur in nursing homes (Håkansson, Öhlén, Morin, & Cohen, ) and 72% of all people who died in Sweden in 2017 were 75 years or older (Statistics Sweden, ), older persons dying of multiple morbidities or “old age” at nursing homes receive insufficient palliative care. This insufficient care may lead to older persons experiencing unnecessary suffering (Fleming et al, ; Smedbäck et al, ) and decreased QoL at the final stage of life.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases usually progress over a period of time, which makes it challenging to determine when an older person's end‐of‐life stage begins (Goddard, Stewart, Thompson, & Hall, ); therefore, early signs preceding death could be difficult for the nursing home staff to detect (Åvik, Sandgren, Fürst, Ahlström, & Behm, ). The end‐of‐life process of older persons has been described as a dynamic individual process (Krishnan, ), and the final year of life is often associated with symptoms such as pain, depression, confusion and distress (Fleming et al, ), leading to decreased QoL. A high proportion of older people die shortly after moving into a nursing home (Schon, Lagergren, & Karleholt, ), and almost one‐third of older persons who move into a nursing home die within six weeks (Smedbäck et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From interviews with relatives after the study participants' deaths, reportedly dying comfortably was associated with avoiding transitions, particularly with staying in care homes that had become home. 5 Qualitative research in the same study found participants aged 95 were willing to discuss their end-of-life care preferences. 6 We also sought to understand bereaved family members' perspectives on their 'older old' relatives' deaths.…”
mentioning
confidence: 99%